On the Evolution and Function of Plasmodium vivax Reticulocyte Binding Surface Antigen (pvrbsa) - Camargo-Ayala, Paola Andrea; Garzón-Ospina, Diego; Moreno-Pérez, Darwin Andrés; Ricaurte-Contreras, Laura Alejandra; Noya, Oscar; Patarroyo, Manuel A. (Frontiers in Genetics, 2018)
The RBSA protein is encoded by a gene described in Plasmodium species having tropism for reticulocytes. Since this protein is antigenic in natural infections and can bind to target cells, it has been proposed as a potential candidate for an anti-Plasmodium vivax vaccine. However, genetic diversity (a challenge which must be overcome for ensuring fully effective vaccine design) has not been described at this locus. Likewise, the minimum regions mediating specific parasite-host interaction have not been determined. This is why the rbsa gene’s evolutionary history is being here described, as well as the P. vivax rbsa (pvrbsa) genetic diversity and the specific regions mediating parasite adhesion to reticulocytes. Unlike what has previously been reported, rbsa was also present in several parasite species belonging to the monkey-malaria clade; paralogs were also found in Plasmodium parasites invading reticulocytes. The pvrbsa locus had less diversity than other merozoite surface proteins where natural selection and recombination were the main evolutionary forces involved in causing the observed polymorphism. The N-terminal end (PvRBSA-A) was conserved and under functional constraint; consequently, it was expressed as recombinant protein for binding assays. This protein fragment bound to reticulocytes whilst the C-terminus, included in recombinant PvRBSA-B (which was not under functional constraint), did not. Interestingly, two PvRBSA-A-derived peptides were able to inhibit protein binding to reticulocytes. Specific conserved and functionally important peptides within PvRBSA-A could thus be considered when designing a fully-effective vaccine against P. vivax.